PajakMedan.com as shopping solutions #just stay at home in Covid-19 epidemic situation in Medan city - Sri Fajar Ayu; Nauly, Meutia (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Pajakmedan.com is a solution for traders and consumers in Medan Pajak Halat to break the chain of transmission of Covid 19. The Halat Market was chosen to be the location for USU's community service in 2020 because it has more impact than other markets. The selected trader is UD. Apni's Chicken Cut becomes a partner of service The problems faced by merchants in the Covid 19 era were sales revenue fell by 25-45 &, high demand for customers to send goods outside of tax, merchants were worried about contracting Covid-1, Pajakmedan.com was expected to increase revenue on covid-19. The target of activities in the short and long term program partners must be able to develop their product market using the taxmedan.com platform. The expected short-term target is an increase in knowledge to traders that their buying and selling activities can be developed online. The long-term target that the team hopes is the implementation of an online buying and selling system using the taxmedan.com site in all traditional markets in Medan City. Despite the emergence of constraints that led to a decline in the number of buyers coming to the market, sales volume remained stable.